2011
DOI: 10.1007/s00228-011-1126-0
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone-induced acute hepatotoxicity

Abstract: Dear Editor, We present the case of a 44-year-old man admitted with central chest pain associated with breathlessness that was not relieved by taking sublingual glyceryl nitrate. He presented with a background of old inferior infarct, dilated cardiomyopathy and poor left-ventricular (LV) function and hypertension. There was history of continued alcohol and cocaine abuse. Electrocardiogram on admission confirmed atrial flutter, ventricular rate of 160 bpm with evidence of heart failure, and systolic blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
1
4
0
3
Order By: Relevance
“…This was in accordance with several case studies in which LV dysfunction was observed. 4 , 7 , 12 , 18 , 19 The same was also found with oral amiodarone. 22 If direct drug toxicity is assumed, LV dysfunction delays amiodarone elimination by prolonging the half life of its metabolites, and therefore might predispose to liver injury.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…This was in accordance with several case studies in which LV dysfunction was observed. 4 , 7 , 12 , 18 , 19 The same was also found with oral amiodarone. 22 If direct drug toxicity is assumed, LV dysfunction delays amiodarone elimination by prolonging the half life of its metabolites, and therefore might predispose to liver injury.…”
Section: Discussionsupporting
confidence: 66%
“…Similarly, heart failure, congestive liver disease, high dose of IV amiodarone, and hypotension from ventricular arrhythmias were observed in patients with AILI among case reports. 4 , 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 8 cases were collected (Table 2). 8,[10][11][12][13][14] According to the currently available documentation, hepatotoxicity usually occurs within 24 hours after starting IV amiodarone administration, but sometimes after more than 3 days. 8 It usually recovers gradually after discontinuing IV amiodarone.…”
Section: Discussionmentioning
confidence: 99%